Uji Antagonisme Jamur Endofit Asal Tanaman Acacia mangium terhadap Fusarium oxysporum Penyebab Penyakit Layu Vaskular - Soleha, Soleha; Anissa, Nabillah; Wulansari, Retno; Erfandari, Ovy (Jurnal Ilmu Alam dan Lingkungan, 2025)
Fusarium oxysporum is a pathogen that causes wilt disease and has a wide host range in various commodities. An alternative to sustainability control that can reduce the application of chemical pesticides is the application of biological agents, such as plant endophytic fungi. This study aimed to explore and examined the potential antagonism of the endophytic fungus A. mangium against F. oxysporum causal agent of wilt disease. This research was conducted at the Plantation Processing Laboratory, Department of Plantation Crops Cultivation, Lampung State Polytechnic from January to March 2025. The research was carried out by exploration and inhibition test. Five isolates of endophytic fungi from the A. mangium were isolated. All isolates inhibit the growth of F. oxysporum by 41.44%-67.78%. The lowest inhibition was produced by isolate AM27 by 41.44%, and the highest inhibition was produced by isolate AM26 by 67.78%. Endophytic fungal isolates that had an inhibition of more than 50% potential to be used as biological agents to control F. oxysporum causal agent of wilt disease in plants.